Vacancy of the Apostolic See - WROCEŃSKI, JÓZEF (Prawo Kanoniczne, 2017)
The paper seeks to explain the situation of the vacancy of the Holy See caused by the death of the pope or his resignation until the election of a new pope. Starting from the analysis of the most important papal documents, especially by the Popes Pius XII, and Paul VI, and of the Constitution of John Paul II, which is currently in use regulating the issue of vacancy in a timely and comprehensive manner, the author discusses the evolution of the legal regulation of the vacancy. What especially matters is the issue of the power of the College of Cardinals to govern the Church during the vacancy, as well as the functioning of the various offices of the Roman Curia. The study leads to the following conclusions: the vacancy of the Apostolic See may occur as a result of the pope's death or resignation from his office. He cannot be deposed or removed from it. This is due to the fact that the pope has the highest office in the Church and there is not another competent person or authority above the pope. During the vacancy, the College of Cardinals handles current affairs, making decisions on two types of meetings: general and particular, while all important matters wait for the new pope. The novelty of the reform of Pope John Paul II is the rotation of Cardinals Assistants constituting a particular meeting.